Analysis of Reading Errors in the Application of the Law of Nun Sukun and Mim Sukun in Grade 6 Students of MI Daarussa'adah in Parungkuda Sukabumi - Yulia Sanica Popy; Mahwa Dalimi; Siti Nurherlina; Sherly Selvianawati; Muhamad Ibnu Malik (Konsultan Jurnal Ilmiah Indonesia, 2025)
Tajwid instruction at the Madrasah Ibtidaiyah level continues to face challenges related to students’ low accuracy in Qur’anic recitation, particularly in the application of the rules of nun sukun and mim sukun. Recitation errors that are not corrected promptly tend to become persistent habits and negatively affect the overall quality of Qur’anic reading. This study aims to analyze the forms of recitation errors in the application of nun sukun and mim sukun rules, identify the recitation rules that are most frequently misapplied, and examine the factors contributing to these errors among sixth-grade students at MI Daarussa’adah Parungkuda Sukabumi. This research employs a qualitative approach with a case study design. Data were collected through observation of students’ recitation during Qur’an learning activities and daily tahfidz sessions, interviews with teachers and students, and supporting documentation. The findings indicate that recitation errors are systematic and recurrent, particularly in the application of ikhfa’, ikhfa’ shafawi, and idgham bighunnah, influenced by limited phonetic mastery, habitual recitation without continuous correction, and learning orientations that prioritize fluency over accuracy. The conclusion emphasizes the importance of balanced integration between tajwid instruction and tahfidz activities. The implications of this study provide a practical foundation for developing more applicable tajwid learning strategies oriented toward improving the quality of students’ Qur’anic recitation.